Electrophysiological Study of Campbell Line Rats Before and After the Administration of Drugs - Mustafa Ogly Kasimov, Elmar; Faizi Kyzy Hashimova, Ulduz; N. Ilnitskiy, Andrey; Nasib Kyzy Mamedzade, Afet; Irshad Kyzy Alieva, Natavan (International Journal of Psychosocial Rehabilitation, 2020)
The study includes the evaluation of the total bioelectric activity of a, b, and c waves of the electroretinogram (ERG) and mean values of the amplitude of b-waves in the retina of Campbell rats of different ages before and after the administration of the drugs (Retinalaminum and Retinalaminum + Omk1). The study results showed that the administration of Retimalaminum and Retinalaminum + Omk1 to neonate rats led to a significant improvement in the total bioelectric activity of the waves a, b, and c of ERG. A significant increase in this parameter value was also observed in neonate rats after the combined administration of Retinalaminum + Omk1 in comparison with the group of rats that received only Retinalaminum. In adult rats, the administration of the abovementioned parameters improved the bioelectric activity of the waves a,b,c of ERG, but there were no significant differences between the administration of Retinalaminum and Retinalaminum in combination with Omk1 revealed. There were no significant data on the improvement of bioelectrical activity in senior rats after the administration of the drugs. The study of the mean values of b-wave in rats of different ages revealed the same consistency as it was observed in the total bioelectrical activity according to ERG.